Urban accessibility in the Historic Center of Santa Maria for people with physical disabilities and/or reduced mobility - Pagnossin, Thais do Amaral; Caldas da Silva, Eliane; Dockhorn, Leonardo da Silva Mello; Maia Borges, Juliana; Rolão Flores, Anelis (Disciplinarum Scientia | Saúde, 2024)
Objective: This study aimed to investigate the accessibility conditions on sidewalks in the Historic Center of Santa Maria, focusing on the inclusion of people with physical disabilities or reduced mobility. Method: This is an exploratory field research with a qualitative approach. A bibliographical survey, photographic records of the sidewalks and interviews with members of the Associação Santa Mariense Paradesportiva were carried out. Data analysis was carried out using the content analysis technique. Results: The results highlighted the difficulties faced by people with physical disabilities or reduced mobility due to the lack of accessibility on sidewalks. This impacts their occupational performance and quality of life. Conclusion. Accessibility is fundamental to guarantee the inclusion and social participation of all people in the city. Urban planning must consider the needs of all citizens, providing a safe and inclusive environment. The Creative District project in Santa Maria aims to improve accessibility, reflecting the importance of inclusion for the city’s growth and sustainable development. This study contributes to identifying problems and suggesting improvements to the competent authorities, promoting inclusion and improving quality of life in a fair and conscious way.